Effect of vitamin D supplementation in patients with chronic hepatitis C after direct-acting antiviral treatment: a randomized, double-blind, placebo-controlled trial - Sriphoosanaphan, Supachaya; Thanapirom, Kessarin; Kerr, Stephen J.; Suksawatamnuay, Sirinporn; Thaimai, Panarat; Sittisomwong, Sukanya; Sonsiri, Kanokwan; Srisoonthorn, Nunthiya; Teeratorn, Nicha; Tanpowpong, Natthaporn; Chaopathomkul, Bundit; Treeprasertsuk, Sombat; et al. (PeerJ, 2021)
Background Replacement of vitamin D (VD) among patients with chronic hepatitis C (CHC) before viral eradication has demonstrated a protective effect on serum markers associated with hepatic fibrogenesis. We therefore hypothesized that VD may facilitate further fibrosis amelioration following curative treatment with direct-acting antivirals (DAA). Methods This study was a randomized, double-blind, placebo-controlled trial conducted between February 2018 and August 2018. Patients with CHC and VD deficiency were randomized in a 1:1 ratio to either receive ergicalciferol or placebo over 6 weeks. Biochemical analysis indicators, including 25-hydroxyvitamin D (25(OH)D), fibrogenic markers [(transforming growth factor beta 1 (TGF-β1) and tissue inhibitors of matrix metalloproteinases 1 (TIMP-1)], and fibrolytic markers [matrix metalloproteinase 9 (MMP-9) and amino terminal type III procollagen peptide (P3NP)], were assessed at baseline and at 6 weeks. Serum 25(OH)D was analyzed by a chemiluminescence immunoassay. Serum hepatic fibrogenesis markers were measured using a quantitative sandwich enzyme-linked immunosorbent assay. Results Seventy-five patients with CHC and VD deficiency were randomly assigned to VD (n = 37) and placebo (n = 38) groups. At the end of the study, the mean serum 25(OH)D level had risen to a normal level in the VD group, but was still deficient in the placebo group (41.8 ± 9.1 vs. 18.1 ± 4.6 ng/mL, p < 0.001). Upon restoration of the VD level, there were no significant mean differences in the change from baseline for TGF-β1 (−0.6 ng/mL (95% confidence interval (95% CI) [−2.8–1.7]), p = 0.63), TIMP-1 (−5.5 ng/mL (95% CI [−26.4 –15.3]), p = 0.60), MMP-9 (122.9 ng/mL (95% CI [−69.0 –314.8]), p = 0.21), and P3NP (−0.1 ng/mL (95% CI [−2.4 –2.2]), p = 0.92) between the VD and placebo groups. Conclusion Short-term VD supplementation after DAA treatment in patients with CHC does not improve serum fibrogenesis markers and may not expedite the residual liver fibrosis healing process. Future studies are warranted to evaluate the long-term effect of VD supplementation on hepatic fibrosis regression.
Keywords: Vitamin D; Hepatitis C; Liver fibrosis; Direct-acting agent; Liver fibrogenesis